APAKAH SKEPTISISME PROFESIONAL, KOMPLEKSITAS TUGAS DAN TEKNIK AUDIT BERBANTUAN KOMPUTER BERDAMPAK TERHADAP KUALITAS AUDIT? - Yuliana Sari; Kurniawati Kurniawati (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract - A quality audit is the ultimate process that the auditors wants to achieve. Auditors must continuiously improve audit quality to maintain the trust of stakeholders. This study aims to find out if professional skepticism, task complexity, and computer-assisted audit techniques have an impact on audit quality. This research model used to analyze data is Structural Equation Modelling (SEM). Research data is the primary data obtained from 67 respondents of external auditors from Public Accounting Firm in the DKI Jakarta Region. The result showed that professional skepticisim and computer assisted audit technique had a significant and positive influence on audit quality, while the complexity of the task had no significant effect on audit quality. The results of this study encouraged the Public Accounting Firm to consider the use of technology as one of the aspects that can improve the quality of audit and synergy it with the profesional skepticism. Keywords: Audit Quality; Computer Assisted Audit Technology; Professional Skepticism; Public Accounting Firm; Task Complexity